Effects of Standardized Ileal Digestible Histidine:Lysine Ratio on Growth Performance of 15- to 25-lb Pigs - H. S. Cemin; R. M. Karns; C. M. Vier; M. D. Tokach; S. S. Dritz; K. J. Touchette; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
Two experiments were conducted to determine the standardized ileal digestible (SID) His:Lys requirement of 15- to 25-lb nursery pigs. A total of 360 and 350 pigs (DNA 241 × 600), initially 15.6 and 14.5 lb body weight (BW), were used in Exp. 1 and 2, respectively. There were 5 pigs per pen and 12 and 10 replicates per treatment in Exp. 1 and 2, respectively. After weaning, pigs were fed a common pelleted diet for 10 d in Exp. 1 and 7 d in Exp. 2. Then, pens were assigned to treatments in a randomized complete block design with BW as the blocking factor. Dietary treatments consisted of SID His:Lys ratios of 24, 28, 32, 36, 40, and 44% in Exp. 1 and 24, 28, 30, 32, 34, 36, and 42% in Exp. 2. Experimental diets were fed in pellet form for 10 d in Exp. 1 and 14 d in Exp. 2 followed by a common mash diet for 15 d in Exp. 1 and 14 d in Exp. 2. Data were analyzed using the GLIMMIX and NLMIXED procedures of SAS. Competing statistical models were quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). In Exp. 1, increasing SID His:Lys increased (quadratic,P<0.001) average daily gain (ADG), average daily feed intake (ADFI), and BW and improved (quadratic,P<0.001) feed-to-gain ratio (F/G). In Exp. 2, ADG increased (quadratic,P= 0.001) and F/G improved (quadratic,P= 0.001) and ADFI linearly increased (P= 0.001) with increasing SID His:Lys. The best-fitting model for all response variables analyzed was the BLL. In Exp. 1, requirement estimates were 29.7%, 29.1%, and 29.8% SID His:Lys for ADG, ADFI, and gain-to-feed ratio (G:F), respectively. In Exp. 2, the SID His:Lys requirements were estimated at 31.0% for ADG and 28.6% for G:F. These results suggest that the NRC may overestimate the SID His:Lys requirement for 15- to 25-lb pigs. Therefore, nursery diets can be formulated with higher inclusion of crystalline amino acids before His becomes limiting.
Keywords: histidine; growth; modeling; swine